RANCANG BANGUN PENAMPIL STATUS KONDISI ANGIN SECARA ONLINE MENGGUNAKAN ARDUINO NANO - Ibtihal, Moch Fahulul; Muslim, Muhammad Aziz; Setyawan, Raden Arief (Jurnal Mahasiswa TEUB, 2024)
Indonesia is the 15th largest country in the world and the largest archipelago in the world. With Indonesia's vast territory, the country has diverse natural conditions so that natural disasters that occur also vary in each region. One of the many natural disasters that occur in Indonesia is strong winds. Strong winds are quite dangerous because they cannot be predicted. This can certainly harm the community. Prevention efforts are very important in dealing with this phenomenon, such as periodic observation of wind speed. The solution to this problem is to design a tool that can provide wind speed information that can be accessed through the website and can provide warnings. The making of this tool consists of the main parts in the form of a microcontroller, wind speed sensor, humidity temperature sensor, and GSM module. The results of the sensor will be processed by a microcontroller to be sent via a GSM module connection and can be accessed using the internet through a website that has been created. From the results of the tool design, if the wind speed ≥11 m / s and wind acceleration ≥ 5.5 m / s then on the website there is a danger sign display and the alarm on the tool will turn on. Keywords— microcontroller, wind speed sensor, GSM module